2013
DOI: 10.2147/dnnd.s36917
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacologic management of depression in Parkinson's disease

Abstract: Depression in Parkinson's disease (PD) is common, and it appears to worsen the motor and cognitive progression of the disease, and limits the patient's quality of life. In this paper, we review the pharmacotherapy of depression in people with PD. We find that evidence is sparse when it comes to this patient population. There is some evidence that older tricyclic antidepressants (nortriptyline and desipramine) may be effective in this population. There is also growing evidence that newer antidepressants like pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Other studies demonstrated that some antiparkinsonian drugs such as dopamine receptor agonists and MAO-B inhibitors like selegiline and rasagiline, when administered in the recommended dose range for the treatment of PD, exerted limited antidepressant efficacy in patients with PD [ 52 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Also, mirtazapine, atomoxetine, and—interestingly—bupropion, a norepinephrine-dopamine reuptake inhibitor antidepressant, are reported as not effective in treating depression in PD patients [ 82 , 85 , 90 , 91 , 92 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies demonstrated that some antiparkinsonian drugs such as dopamine receptor agonists and MAO-B inhibitors like selegiline and rasagiline, when administered in the recommended dose range for the treatment of PD, exerted limited antidepressant efficacy in patients with PD [ 52 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Also, mirtazapine, atomoxetine, and—interestingly—bupropion, a norepinephrine-dopamine reuptake inhibitor antidepressant, are reported as not effective in treating depression in PD patients [ 82 , 85 , 90 , 91 , 92 ].…”
Section: Introductionmentioning
confidence: 99%